Teeth whitening influence for oral tissues and teeth - Šveckutė, Agnė; Mameniškis, Valdas (Slauga. Mokslas ir praktika, 2020)
The aim of this study – to evaluate the impact of teeth whitening for oral soft tissues and teeth. Materials and methods. The qualitative study was conducted: the case study, applying intraoral examination, tooth shade setting with dental palette, cold air flow test for research participants and interview with them. The research was attended by 4 patients, who wishing to perform a teeth whitening procedure at home with: a teeth whitening pencil, a toothpaste and tombs, and at dental office with UV rays that are regenerated by an LED lamp. Into the research were involved people, who want to make a whitening procedure at home: with whitening pen, teeth powder and whitening guards, also teeth whitening at the dentist’s office using ultraviolet rays which regenerates LED lamp. The purposive sample of research participants was applied. Insights. Before the teeth whitening procedure the soft tissues of the oral of patients, who participated in the research, were healthy and not damaged. The teeth shade of all research participants was individual. The patient, who whitening the teeth at the dentist’s office by UV rays, was felt teeth sensitivity after the teeth whitening procedure. The teeth shade has changed almost for all research participants. The teeth whitening procedure at the dentist’s office with UV rays has the greatest impact on the teeth shade. The smallest effect on the teeth shade was made by the toothpaste. The teeth sensitivity was caused by the teeth whitening procedure at the dentist’s office with UV rays. The research participants said that it was uncomfortable to use a tooth whitening pencil and toothpaste for the teeth whitening.